Cover Picture: Triptycene‐Roofed Quinoxaline Cavitands for the Supramolecular Detection of BTEX in Air (Chem. Eur. J. 10/2016). Issue 10 (12th January 2016) - Bertani, Federico; Riboni, Nicolò; Bianchi, Federica; Brancatelli, Giovanna; Sterner, Elizabeth S.; Pinalli, Roberta; Geremia, Silvano; Swager, Timothy M.; Dalcanale, Enrico
Abstract : Environmental monitoring of benzene and related volatile aromatic compounds (benzene, toluene, ethylbenzene, and xylenes: BTEX) is a challenging goal owing to the conflicting requirements of molecular‐level selectivity and low‐ppb sensitivity. Newly developed solid‐phase microextraction (SPME) fibers that are coated with suitably designed triptycene‐roofed quinoxaline cavitands outperform commercial coatings in selective BTEX adsorption and meet the strict standards set by European Union legislation for environmental monitoring of benzene. More information can be found in the Full Paper by E. Dalcanale, T. M. Swager et al. onpage 3312 ff.